2011
DOI: 10.1007/s00170-011-3563-4
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of fabrication of micro devices by electrochemical micromachining (ECMM) and its finishing by magnetorheological fluid

Abstract: Electrochemical micromachining (ECMM) is an advanced machining process for machining of electrically conducting materials. In the present work, a micro nozzle and a fluidic mixer having complex structures are made using masking technique by ECMM process. Mask is made of 50-μm transparent sheet and the micro nozzle and micro mixer are fabricated on an 800-μm thick copper sheet. The resulting rough inner walls and bottom surface of micro nozzle are finished using magnetorheological fluid-based finishing process.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The relative motion between the stiffened MR fluid and workpiece results in material removal (finishing or deburring) from the workpiece. MR fluids with the addition of different types of abrasive particles are successfully used for finishing of a variety of materials such as optical glass, 30 metallic components such as knee joint implant, 31 micronozzles, 32 deburring of microgroves 33 and so on. In the present case, abrasive particles are not used along with CIPs as they may damage the microchannel due to soft workpiece material.…”
Section: Methodsmentioning
confidence: 99%
“…The relative motion between the stiffened MR fluid and workpiece results in material removal (finishing or deburring) from the workpiece. MR fluids with the addition of different types of abrasive particles are successfully used for finishing of a variety of materials such as optical glass, 30 metallic components such as knee joint implant, 31 micronozzles, 32 deburring of microgroves 33 and so on. In the present case, abrasive particles are not used along with CIPs as they may damage the microchannel due to soft workpiece material.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that masking of the workpiece reduces undercut and improves accuracy of the micro machined features. 18,19 Therefore, a water insoluble adhesive is used and spread over the workpiece and mask, and then it is firmly pressed for several minutes. The mask is made of a 50 µm plastic sheet and laser machining is done for cutting of the desired features on the mask to localize the machining area.…”
Section: Fabrication Of Micro Patternmentioning
confidence: 99%
“…64 Figure 6 shows a micromixer fabricated using ECMM process and the width of the microchannel ranging between 180 and 300 μm. 65…”
Section: Microsubtractive (Micromachining) Processesmentioning
confidence: 99%